2019
DOI: 10.1111/jar.12602
|View full text |Cite
|
Sign up to set email alerts
|

What do parents expect from a genetic diagnosis of their child with intellectual disability?

Abstract: Background Caring for a child with intellectual disability (ID) has been associated with increased social and psychological burdens. Diagnostic and prognostic uncertainty may enhance emotional stress in families. Method The present authors assessed the motivations, expectations, mental health, physical health and the quality of life of 194 parents whose children with intellectual disability were undergoing a genetic diagnostic workup. Results Most parents considered a diagnosis highly relevant for their own em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Adult and pediatric diagnosed focus groups were clear about the significance of receiving a diagnosis through the UDN. Based on prior research, we know the diagnostic odyssey is often a difficult, uncertain time and most are hopeful for a diagnosis as opposed to living in a state of unknown [ 7 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult and pediatric diagnosed focus groups were clear about the significance of receiving a diagnosis through the UDN. Based on prior research, we know the diagnostic odyssey is often a difficult, uncertain time and most are hopeful for a diagnosis as opposed to living in a state of unknown [ 7 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first theme highlighted that the parenting work of obtaining medical recognition is slow and uncertain due to the rarity and various forms of PIMD. Access to medical recognition allows parents to meet the emotional challenges generated by the absence of a diagnosis and to project themselves in terms of future (grand)parenthood, access to health care, and coordination of care 29–31 . Because PIMD is a syndromic entity that involves many possible etiologies as time passes (e.g., neurodevelopmental delay), a PIMD diagnosis may be a long‐term process over many months or years.…”
Section: Discussionmentioning
confidence: 99%
“…When you go for one medical condition or another and there is in fact [PIMD], they will treat the condition he's in hospital for, but for all the others parenthood, access to health care, and coordination of care. [29][30][31] Because PIMD is a syndromic entity that involves many possible etiologies as time passes (e.g., neurodevelopmental delay), a PIMD diagnosis may be a long-term process over many months or years.…”
Section: Themes Identifiedmentioning
confidence: 99%
“…Previous international studies show that being exposed to cumulative risk factors may lead to reduced psychological adjustment and academic achievement (Forehand, Biggar, & Kotchick, 1998). Studies from other national contexts investigated the effect that having a child with SEN has on parents, often concluding that additional supports are needed (Dikow et al, 2019;Thomas et al, 2018). Data from the Longitudinal Study of Australian Children has shown that mothers of children with chronic illness (Quach & Barnett, 2005) and special needs (Quach, Jansen, Mensah, & Wake, 2015) have poorer mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%